Publicizing the survey image in local consumer protection the mission program is a model (Al-Academy, 2023)
The investigative film is part of the documentary films and is considered one of the important films that have a high viewership by the recipient, which is of great importance in transmitting information and contributing to creating awareness of the community through the advertising function performed by the cinematic image, as the researcher addresses the concept of advertising and its development through the time stages. And advertising functions. Then the researcher dealt in his research with the cinematic technical elements that contribute to the success of the investigative advertising work, such as camera movements, music, sound effects, dialogue ... etc., which enrich the investigative picture with realism and the flow of information in a smooth and logical manner, creating an atmosphere of anticipation, tension and curiosity for the recipient.